PENGARUH PARTISIPASI PENGANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN INFORMASI ASIMETRI DAN KEKOHESIVAN KELOMPOK SEBAGAI VARIABEL MODERASI (Studi Empiris pada Pemerintah Kabupaten Kampar) - Robinka Gultom; Zulbahridar Zulbahridar; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Public sectors use performance-based budgeting system that is an efficient and participation development process, and use performance as a benchmark for the achievement of local goverment’s budgeting target. However, the performance-based assessment motivates agents to perform budgetary slack for the sake of a better future career. The purpose of this research is to explore the influence of budgeting participation and budget goal clarity on budgetary slack with information asymmetry, and group cohesiveness as moderating variables. The population of this research was 45 SKPD offices of Kampar Regency. This research use purposive sampling with the final sample of 84 participants. This research use primary data bu disseminating the questionnaire. Multiple linear regression and MRA was used in this research as technical analysis to test the hypothesis. The result of this research showed that budgetary participation and budget goal clarity significantly influenced budgetary slack. Information asymmetry as a moderating variables was able to influence the relationship between budgetary participation to budgetary slack and budget goal clarity to budgetary slack. Group cohesiveness as a moderating variable was able to influence the relationship between budgetary participation to budgetary slack. At the same time, group cohesiveness was unable to influence the relationship between budget goal clarity and budgetary slack.Keywords : Budgetary Participation, Budget Goal Clarity, Information Asymetry, Group Cohesiveness, Budgetary Slack.